Validity of Self-Reported Height, Weight and Body Mass Index Among Cypriot Adolescents: Accuracy in Assessing Overweight Status and Weight Overestimation as Predictor of Disordered Eating Behaviour - Charalampos, Hadjigeorgiou; Tornaritis , Michael; Solea , Antonia; Savva, Savvas; Kafatos, Antonis (Mediterranean Journal of Social Sciences, 2012)
Aim: the aim of the present study was to assess the validity of self-reported weight and height among Cypriotadolescents. Method: Adolescents’ weight and height was measured during school. Students completed the questionnairesEAT-26 and EDI-3. Results: self-reported and measured weight and height are highly correlated. Boys underreport their weightby 0.28 kg and over report their height by 0.84 cm; girls underreport their weight by 0.91 kg and over report their height by 1.52cm. 8% of overweight adolescents would have been neglected if self-report measures were relied upon. Overweight adolescentsmake greater self-report errors in BMI in comparison to their normal/ underweight counterparts. Adolescents who overestimatedtheir weight by 5% had lower scores on Drive for thinness scales and Body dissatisfaction scales. Conclusion: relying on selfreportestimates of height and weight can lead to erroneous conclusions of prevalence estimates of overweight and obesityamong Cypriot adolescents and must be used with caution.